Security Visiting: RFID-Based Smartphone Indoor Guiding System. (19th January 2014) - Zeng, Hong; Zhang, Jianhui; Dai, Guojun; Gao, Zhigang; Hu, Haiyang
Abstract : This paper presents a security visiting guiding system SVG composed of RFID, smart phone, and Wi-Fi signal widely available. The SVG system can provide visitors with the map of a given building, so that the visitor can easily find the target under its guide. It can also protect user's privacy location information by cryptographic two-dimension code and RFID. The two-dimension code can be easily obtained by a mobile phone and it authorizes a visitor to obtain the navigation service of SVG. The visitor receives the permission from his host and makes a date through SVG. Then, SVG will navigate both the persons to meet at any place in the building. Furthermore, this paper demonstrates and evaluates the SVG security scheme. We conduct an attacker model and test the ability of the scheme in protecting user's location security.